2014
DOI: 10.1007/s10750-014-1894-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of benthic invertebrates downstream of hyperalkaline steel slag discharges

Abstract: This study assesses the physical and chemical characteristics of hyperalkaline steel slag leachate from a former steelworks on two streams in England and their impacts on 24 benthic invertebrate communities. Using multivariate methods (CCA), we related 25 invertebrate richness and diversity with chemical parameters along the environmental 26 gradient from point sources to less impacted sites downstream. Point discharges are characterised by high pH (10.6-11.5), high ionic strength (dominated by Ca-CO3-OH 28 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Hydrochemistry at each of the sampling sites on the day of sampling is summarized in Table 1, and is consistent with previous (Mayes et al, 2008) and more recent (Hull et al, 2014;Riley and Mayes, 2015;Hobson et al, 2018;Mayes et al, 2018) monitoring of these systems. Some calcium is sourced from background seepage of karst groundwater into both streams, but the majority is derived from steel slag leachate in the form of Ca(OH) 2 .…”
Section: Hydrochemistrysupporting
confidence: 81%
See 1 more Smart Citation
“…Hydrochemistry at each of the sampling sites on the day of sampling is summarized in Table 1, and is consistent with previous (Mayes et al, 2008) and more recent (Hull et al, 2014;Riley and Mayes, 2015;Hobson et al, 2018;Mayes et al, 2018) monitoring of these systems. Some calcium is sourced from background seepage of karst groundwater into both streams, but the majority is derived from steel slag leachate in the form of Ca(OH) 2 .…”
Section: Hydrochemistrysupporting
confidence: 81%
“…Total alkalinity shows the same enhancement at proximal sites (55-59 mg.L −1 in Dene Burn and 264-332 mg.L −1 in Howden Burn). Given this water composition, it is unsurprising that calcite saturation index is very high (+0.04 to +2.47), and mineral precipitation is high enough to be lethal to local microbenthos by smothering (Hull et al, 2014).…”
Section: Hydrochemistrymentioning
confidence: 99%
“…Several studies have confirmed the negative influence of limed waters on aquatic life [18][19]. The leachate and groundwater pH is above the regulatory threshold for discharge to water bodies.…”
Section: Environmental Implication Of Element Distribution In the Systemmentioning
confidence: 96%
“…battery disposal, use of biosloids, aluminum processing, glass and ceramic production (Enghag 2008, Al-Thyabat et al 2013, Hull et al 2014 raises the question to what extent this will lead to environmental pollution. High lithium concentration in solutions can be toxic to plants (Bradford 1963).…”
Section: Introductionmentioning
confidence: 99%